The Family in a changing world : women, children, and strategies of intervention - Heredia, Rudolf C.; Mathias, Edward; Indian Social Institute (New Delhi : Indian Social Institute, 1995)
With reference to India; contributed articles.
"This is a sponsored publication of Indian social Institute, New Delhi, no. 56/95."
Includes bibliographical reference and index.
Keywords: Women -- India; Patriarchy -- India; Families -- India -- History; Child labor -- India